Investment in Cocoa Planting and Rehabilitation by Cocoa Farmers in Nigeria - Segun, Olowolaju Philip (Asian Journal of Economics and Empirical Research, 2016)
The paper examined investment in cocoa planting and replanting by cocoa farmers in Nigeria. The study sample comprised of 400 cocoa farmers selected from five major cocoa producing states in Nigeria of which 321 farmers responded. Questionnaire technique supplemented by oral interview was used for the study. The data were analysed using multiple regression, Likert rating and percentages. The results show that few cocoa farmers invested in new planting and replanting programme. There is no positive relationship between percentage of annual income invested in new planting and replanting by the cocoa farmers and the number of hectares of farm holding while age of farmers , years of experience as a cocoa farmer and average annual income show marginal positive relationship, however, farmers education has very high positive relationship with a coefficient of 0.935. The result also shows that the independent variables (farmer annual income, number of hectares owned by the farmers, age of the farmers, education and experience of the farmers) have marginal impact on the dependent variable with coefficient of variation of 0.033. The study concluded that cocoa farmers did not invest adequately in new planting and replanting because of lack of capital and non ploughing lack of capital and low ploughing back of kincome due to low income and social needs.